Diversity of aquatic invertebrates associated to Bromeliaceae in the mountain cloud forest - OSPINA-BAUTISTA, FABIOLA; ESTÉVEZ-VARÓN, JAIME V.; REALPE, EMILIO; GAST, FERNANDO (Revista Colombiana de Entomología, 2008)
The aquatic invertebrate community associated with the water tank bromeliads Tillandsia turneri and T. complanata was studied in a mountain cloud forest to determine differences in the invertebrate community and relate those to morphological and physicochemical parameters of the bromeliads. Nineteen individuals of each Bromeliaceae species were sampled, and for each one the aquatic invertebrate community, the water content, litter amount and the morphological and physicochemical parameters were assessed. A total of 23 invertebrate morphospecies were found, of which the order Diptera was the most diverse and abundant; some genera were only found in one of the Bromeliaceae species. The aquatic invertebrate community was similar between the two species. For T. complanata, leaf width and litter amount was related to species number. For T. turneri, the Margalef richness was explained by a model that included the variables of number of leaves, pod width and water content.